Implementasi Bidan Desa terhadap Program Keluarga Berencana (KB) Dalam Pemberdayaan Masyarakat di Desa Serijabo Kecamatan Sungai Pinang Kabupaten Ogan Ilir - Suryati Suryati; Muzaiyanah Muzaiyanah; Lisa Lodia (Journal of Innovative and Creativity, 2025)
This study aims to analyze the implementation of family planning programs (KB) carried out by village midwives in community empowerment in Serijabo Village, Sungai Pinang District, Ogan Ilir Regency. The high rate of population growth is a major challenge in development, especially in improving people's welfare. Village midwives play an important role in providing education, reproductive health services, and counseling to the community to support the success of family planning programs. The purpose of this study is to analyze the implementation of village midwives in increasing public knowledge and awareness about family planning (KB) programs and to analyze the strategies of village midwives in increasing community participation and acceptance of family planning (KB) programs. This research uses a qualitative approach with interview, observation, and documentation methods. The subjects of the study include village midwives, couples of childbearing age (PUS), and community leaders. The results of the study show that the implementation or actions taken by village midwives in increasing public knowledge and awareness of family planning programs are counseling or socialization, collaboration with religious leaders, ease of access, and overcoming social and cultural challenges. Strategies carried out by village midwives include active socialization, provision of reproductive health services, and local culture-based approaches. This study recommends increasing the intensity of socialization by village midwives, collaboration with community leaders, and optimizing government support in the provision of health facilities. Effective implementation is expected to increase community participation in planning programs and support efforts to control population growth for the sake of common welfare. In conclusion, the success of the implementation of the family planning program in Serijabo Village is greatly influenced by the collaboration between health workers, the community, and religious leaders. Improved communication, education, and access to family planning services are needed to optimize the outcomes of this program.